A construction project planning tool based on unit price estimating - Zaragoza, Jesús; González, José; Díaz, José (Revista Ingeniería de Construcción, 2005)
Cost estimating of construction projects in Mexico is generally based on the unit price system. Usually, construction firms commit a great deal of effort to such a task giving little importance to the planning aspects of the project. Nowadays, it appears that while evaluating bidders, owners pay attention primarily to economic issues of the bids and to the completion date of the project, minimizing the importance of the planning function. In this paper a tool to build up comprehensive plan and budget for contractors from a unit price estimate called “AsigRec” is discussed. The tool discussed here is software that allows to show all cost concepts of a cost estimate broken down into a tree diagram. The tree diagram displays graphically the most common levels used to integrate cost estimates in Mexico in a hierarchically fashion: 1) project, 2) item, 3) unit price and, 4) resources. Concurrently, the program allows creating the activity work break down structure (AWBS) in an easy and convenient way. Once the AWBS is defined, it is possible to arrange graphically the way in which the resources established in the original cost estimate will be allocated to new activities. This can be done with the tool by defined vectors named Allocation Operations (AO). Furthermore, the tool generates an Activity Resource Accounts Catalog (CCRA in Spanish). The resulting CCRA could be much simpler than the original cost estimate, allowing an easier project control based on the contractor’s criteria or priorities. The end goal of the tool is to provide the contractor with timely and meaningful information in order to improve his decision making